1999
DOI: 10.1111/j.1600-0773.1999.tb02023.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Vecuronium‐Induced Tetanic Fade in the Isolated Rat Muscle

Abstract: Abstract:The cellular mechanisms underlying the effects of vecuronium on the tetanic contraction were studied in vitro with a combination of myographic and electrophysiologic techniques. We used the isolated sciatic nerve extensor digitorum longus muscle preparation of the rat. Indirect twitches were evoked at 0.1 Hz pulses and tetani at 50 Hz pulses. Trains of end-plate potentials were generated at 50 Hz. The electrophysiological variables used in the analysis of the end-plate potentials were: amplitude, teta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The descending tension is termed TF. Possible mechanisms of TF include depressing ACh mobilization during tetanic stimulation [11], reducing the mean length of time that the AChR-ion channel complex is open by blocking the open ion channels [2,15], and decreasing the available AChRs by occlusion and desensitization [16]. …”
Section: Discussionmentioning
confidence: 99%
“…The descending tension is termed TF. Possible mechanisms of TF include depressing ACh mobilization during tetanic stimulation [11], reducing the mean length of time that the AChR-ion channel complex is open by blocking the open ion channels [2,15], and decreasing the available AChRs by occlusion and desensitization [16]. …”
Section: Discussionmentioning
confidence: 99%
“…At this point, it is interesting to compare these atracurium data with those corresponding to other neuromuscular blockers previously studied in this laboratory: hexamethonium (Gallacci & Oliveira 1990), pancuronium (Gallacci & Oliveira 1994) and vecuronium (de Oliveira & Oliveira 1999). All of them induced fade of tetanic contraction via a summation of pre‐ and postsynaptic effects.…”
Section: Discussionmentioning
confidence: 99%
“…This permitted us to compare atracurium, with regard to cellular mechanisms underlying the fade of the tetanic contraction, with a number of different blockers of neuromuscular transmission which have been previously studied in this laboratory: hexamethonium (Gallacci & Oliveira 1990), pancuronium(Gallacci & Oliveira 1994) and vecuronium(de Oliveira & Oliveira 1999). This comparison is important since we have demonstrated that the cellular mechanisms underlying the effect of these agents on the tetanic contraction differ from compound to compound(Gallacci & Oliveira 1990 & 1994; de Oliveira & Oliveira 1999). In the case of hexamethonium a postsynaptic blocking effect was the main cause of the tetanic fade (Gallacci & Oliveira 1990) while regarding pancuronium (Gallacci & Oliveira 1994) and vecuronium (de Oliveira & Oliveira 1999) both induced fade of tetanic contraction via a summation of pre‐ and postsynaptic blocking effects that were not as different in potency, as they were in the case of hexamethonium (Gallacci & Oliveira 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These two compounds had their cellular effects scrutinized, in this laboratory, using electrophysiological techniques and were found to display differential effects at the neuromuscular junction [14,15]. These two compounds had their cellular effects scrutinized, in this laboratory, using electrophysiological techniques and were found to display differential effects at the neuromuscular junction [14,15].…”
Section: Discussionmentioning
confidence: 99%